Economic geography of contagion: A study on Covid-19 outbreak in India - Tanika Chakraborty; Anirban Mukherjee (Global Labor Organization (GLO), 2022)
We propose a regional inequality-based mechanism to explain the heterogeneity in the spread of Covid-19 and test it using data from India. We argue that an area characterized by coreperiphery economic structure creates regional inequality in which the periphery remains dependent on the core for the supply of jobs, goods and services. Hence, areas arranged in coreperiphery structure induce greater degree of mobility which in turn ends up at a higher infection rate than the more homogeneously developed areas at the time of pandemic. Using nightlights data to measure regional inequality in the degree of economic activity, we find evidence in support of our hypothesis. Further, we find that regions with higher nightlight inequality also experience higher spread of Covid-19 only when lockdown measures have been relaxed and movement of goods and services are near normal. Using mobility data, we provide direct evidence in support of our proposed mechanism; that the positive relationship between regional inequality and Covid-19 infection is driven by mobility. Our findings imply that policy responses to contain Covid-19 contagion needs to be heterogeneous across India where the priority areas can be chosen ex-ante based on inequality in economic activity.
Keywords: I15; I18; R1; 330; Covid-19; contagion; core-periphery; nightlight; mobility